2015
DOI: 10.1158/1535-7163.mct-14-0653
|View full text |Cite
|
Sign up to set email alerts
|

Improved Circulating Tumor Cell Detection by a Combined EpCAM and MCAM CellSearch Enrichment Approach in Patients with Breast Cancer Undergoing Neoadjuvant Chemotherapy

Abstract: Circulating tumor cells (CTC) are detected by the CellSearch System in 20% to 25% of patients with primary breast cancer (pBC). To improve CTC detection, we investigated melanoma cell adhesion molecule (MCAM) as enrichment marker next to epithelial cell adhesion molecule (EpCAM) and tested the clinical relevance of MCAM-positive CTCs in patients with HER2-negative stage II/III pBC starting neoadjuvant chemotherapy (NAC) in the NEOZOTAC trial. Using the CellSearch System, EpCAM-positive and MCAM-positive CTCs w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 21 publications
1
43
1
2
Order By: Relevance
“…Characterization of these cells verified the presence of multipotent cells responsible for genetic and phenotypic heterogeneity, endowing them with strong metastatic potential. In addition, six genes (AGR2, CEACAM5, CLDN3, KRT18, EpCAM and FGFR3) were detected as differentially expressed in the generated CTC cell lines, which was similar to primary CRC cells grown under similar conditions (Smirnov et al, 2005;Mostert et al, 2015;Onstenk et al, 2015). The CTC lines also displayed enhanced drug/xenobiotics metabolizing activity, in particular via cytochrome P450 pathway, suggesting resistance to conventional therapies.…”
Section: Ctc Characteristics As a Snapshot Of Tumor Heterogeneitymentioning
confidence: 68%
“…Characterization of these cells verified the presence of multipotent cells responsible for genetic and phenotypic heterogeneity, endowing them with strong metastatic potential. In addition, six genes (AGR2, CEACAM5, CLDN3, KRT18, EpCAM and FGFR3) were detected as differentially expressed in the generated CTC cell lines, which was similar to primary CRC cells grown under similar conditions (Smirnov et al, 2005;Mostert et al, 2015;Onstenk et al, 2015). The CTC lines also displayed enhanced drug/xenobiotics metabolizing activity, in particular via cytochrome P450 pathway, suggesting resistance to conventional therapies.…”
Section: Ctc Characteristics As a Snapshot Of Tumor Heterogeneitymentioning
confidence: 68%
“…The impact of EMT-associated EpCAM downregulation on CTC detection by EpCAM-dependent techniques, such as the CellSearch Ò system, has been repeatedly reported. Although most of BC subtypes can be efficiently captured by EpCAMbased assays (Ring et al, 2015), several EMT-related antigens have been successfully investigated in addition to EpCAMbased immunoselection as an effective way to increase CTC detection (Mostert et al, 2012Onstenk et al, 2015a;Satelli et al, 2015).…”
Section: Ctc and Epithelialemesenchymal Transitionmentioning
confidence: 99%
“…However, the predictive value of CTCs for NCT response remains controversial. CTC detection clinical trials based on the CellSearch® system suggested EpCAM-positive CTC counts were not correlated to pCR in NCT [21,22]. Our previous study demonstrated that systemic adjuvant chemotherapy had a significant impact on CTCs, as assessed via RT-PCR, and this effect was observed after three cycles of chemotherapy [7].…”
Section: Discussionmentioning
confidence: 95%